Regulatory support of children’s safety on the Internet: experience of the European Union - Vedenieva, Oleksandra A. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The author examines children’s safety on the Internet, measures of its providing and the EU experience in this field. Also attention is paid to activity of the non-government organizations that take part in the providing children’s safety on the Web. Regulatory support of information safety of the children is determined as one of the priority direction of the EU policy.